What are the Characteristics of Learners and the Variations of Non-Electronic Learning Media? - Ira Mahartika; Syukriyati Na'imatul Aisyah; Langen Nidhana Meisyalla; Aldeva Ilhami (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Analysis of media needs is crucial before developing a learning media product. This analysis should immediately look at a need in the field and consider the media according to the criteria and characteristics needed, but this is still ruled out and deemed unnecessary. This study aimed to analyze information about special needs analysis on non-electronic media. This research is a quantitative descriptive study using the NVIVO Plus assisted survey method. The sampling selection is a total of 23 schools were obtained consisting of 23 teachers and 230 students. Data collection were carried out through interviews and questionnaires. The results of the study showed that variations in learning media are still not visible due to the various obstacles encountered by teachers. Students want a variety of non-electronic learning media that is interesting, practical, fun, and easy to understand. Some schools still need non-electronic learning media to support the chemistry learning process, one of which is educational game media, modules, and worksheets based on learning model approaches, as well as a combination of the utility of non-electronic and electronic media.